2015
DOI: 10.1227/neu.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Citation Climate in Neurosurgical Literature and Description of an Interfield Citation Metric

Abstract: G1, group 1G2, group 2G3, group 3G4, group 4IFCM, interfield citation metric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Similar to previous bibliometric analyses, [ 16 18 , 21 ] literature search was conducted in the database of Web of Science (WoS) (Thomson Reuters, New York) on November 15th, 2016. The keywords were “lumbar NEAR pain,” “back pain,” “dorsalgia,” “backache,” “lumbago,” “back NEAR disorder,” and “discitis.” The published time was limited from 1995 to 2016, without other restrictions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous bibliometric analyses, [ 16 18 , 21 ] literature search was conducted in the database of Web of Science (WoS) (Thomson Reuters, New York) on November 15th, 2016. The keywords were “lumbar NEAR pain,” “back pain,” “dorsalgia,” “backache,” “lumbago,” “back NEAR disorder,” and “discitis.” The published time was limited from 1995 to 2016, without other restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…As important indicators, the number of published articles and citation reports have been acknowledged and frequently used to assess worldwide research productivity. [ 13 16 ] Bibliometric analysis was an important tool to measure scientific outputs of an individual, institution or country using relevant parameters including the number of published articles and citation of published articles. [ 17 , 18 ] Besides, bibliometric analyses could roughly investigate the trend of one specific topic and were frequently used in biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
“…Madhugiri et al demonstrated that the time for neurosurgical articles to peak in citations is about 6.25 years after publication. 19 Therefore, later articles in the discrete publication collection time period do not have adequate time to accumulate citations. We felt that adding approximately 18 months was a fair compromise that allowed us to present a metric that encompassed a contemporary time frame and also allowed later articles in the discrete time frame to accumulate citations so as to more adequately reflect the impact or interest generated by that article.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has also been demonstrated that the time to peak citation does not differ between articles in neurosurgical journals compared with those in nonneurosurgical high-impact journals, so there should be no bias in our methodology against either. 19 The second methodological improvement was to directly contact every program to obtain faculty affiliations for each year in the discrete time frame. Previously, faculty names were collected from program websites.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, if P i were to be the average publications per year for a particular institute i and P 0 -the national average of P i , the normalized publication performance (NPP) would be given by following formula that has been described previously-NPP i 0 0 = P P P [14] • The quality of original work being published from the institutes was assessed as follows -institutes were first divided into quartiles based on the number of original papers published. All original papers published by institutes in the highest quartile were listed, and the citations received by these papers were determined.…”
Section: Methodsmentioning
confidence: 99%